PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Pradana, Bayu Ilham; Ardiyansyah, Ahmad Irwan (Jurnal Kewirausahaan dan Inovasi, 2022)
The purpose of this study is to identify the effects of organizational culture, leadership and work motivation on employee performance. This quantitative research is categorized as explanatory research because it explains the causal relationship between variables through hypothesis testing. The data was collected through questionnaires distributed to 75 employees of Kusuma Agrowisata Batu Hotel and was analyzed using multiple regression analysis in SPSS. The results of the t test are that organizational culture has the values of 3.451, that leadership has the values of 3.681, and that motivation has the value of 2.394; all of which are positive indicating unidirectional relationship. Using the t table of 1.994, it can be concluded that organizational culture, leadership, and motivation positively and significantly affect employee performance. Therefore, Kusuma Agrowisata Batu Hotel needs to enhance those factors since they have been proven to affect employee performance.